Network response time : Case study UUM ISLAN - Abas, Azizi; Din, Roshidi; Osman, Baharudin (Universiti Utara Malaysia, 2007)
This research was done descriptively in order to collect data about bandwidths, errors, traffics and ping latencies inside Integrated Sintok Local Area Network (ISLAN).The samples of study are restricted to the applications in University Information System (SMU).The data obtained through interview sessions with inter-varsity and distributed questionnaires were referred to as guidelines for network monitoring process using Cacti application.The data, which were recorded every five minutes by Cacti application, were analyzed.The data monitored by Cacti were packet inputs, packet outputs, errors in, errors out and total time connected in seconds.At the end of this study, few suggestions were presented in order to improve the SMU usage.